Polypropylene resin expanded beads and polypropylene resin expanded beads molded body

By using multi-layer polypropylene resin foam particles, combining the core layer of low-melting and high-melting polypropylene resin and the auxiliary components of high-melting polypropylene resin, the foam particles formed can maintain high rigidity and high porosity within a wide pressure range, solving the problem of the traditional method reducing porosity under high pressure, and achieving efficient molded body production.

JP7664860B2Active Publication Date: 2025-04-18JSP CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021575710
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-04
Filing Date
2021-01-21
Publication Date
2025-04-18
Estimated Expiration
2041-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to form a polypropylene resin foam particle molded body with high rigidity and high porosity under both low pressure and high pressure conditions, and the traditional method can easily lead to a decrease in the porosity of the molded body under high pressure.

Method used

Multi-layer polypropylene resin foam particles are used, and the core layer is composed of low-melting and high-melting polypropylene resin. The foam particles formed have a pore structure and a cover layer to ensure that high porosity and rigidity can be maintained under different pressure conditions.

Benefits of technology

It is realized that polypropylene resin foam particles can form high rigidity and high porosity molded bodies within a wide pressure range, avoiding the problem of decreasing porosity under high pressure, and improving the mechanical properties and scope of application of the molded bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664860000008
    Figure 0007664860000008
  • Figure 0007664860000009
    Figure 0007664860000009
  • Figure 0007664860000010
    Figure 0007664860000010
Patent Text Reader

Abstract

Foam particles: having through holes; comprising a foam core layer made of a resin composition that comprises two polypropylene resins that form the through holes and have different melting points, and a coating layer that coats the foam core layer and is made of a polyolefin resin; and exhibiting a DSC curve in which the endothermic peak unique to the resin composition and the endothermic peak on the higher temperature side from the endothermic peak appear in a specific heat of fusion ratio.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to expanded polypropylene resin beads having through holes, and to an expanded polypropylene resin bead molding having interconnected voids, which is obtained by molding the expanded beads in a mold. [Background technology]

[0002] A polypropylene resin foamed bead molding having interconnected voids (hereinafter, simply referred to as a foamed bead molding having voids, or foamed bead molding) has excellent water permeability, breathability, sound absorption, and cushioning properties, and is therefore used as drainage materials, wall materials in buildings, automotive interior materials, and the like. Furthermore, in recent years, foamed bead moldings having voids have also come to be used as automotive seat members because of their excellent adhesion to polyurethane foam. An example of such a foamed molding used as an automotive seat member is disclosed in Patent Document 1.

[0003] In recent years, there has been a demand for a foamed bead molding having higher rigidity while maintaining a porosity. As a method for obtaining a foamed bead molding having excellent rigidity, it has been considered to use a polypropylene resin having a high melting point, but since a high vapor pressure is required for molding the foamed polypropylene resin having a high melting point in a mold, there is a problem that molding in a mold at a low vapor pressure is difficult.

[0004] In response to these problems, Patent Document 2 describes expanded propylene-based resin beads having a cylindrically shaped expanded core layer and a coating layer that coats the expanded core layer, in which the core layer is made of a resin that is a mixture of a propylene-based resin with a low melting point and a propylene-based resin with a high melting point in a specific ratio, and the coating layer is made of an olefin-based resin with a melting point lower than that of the core layer, thereby enabling the expanded beads to be molded in a mold at low pressure to produce a porous expanded bead molding with excellent rigidity. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-30597 A [Patent Document 2] U.S. Patent No. 10,487,188 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the expanded beads disclosed in Patent Document 2 have a limited range of vapor pressure at which an expanded bead molding having a high porosity can be produced in a mold. Specifically, when the expanded beads described in Patent Document 2 have a high vapor pressure during molding in a mold, the porosity of the resulting expanded bead molding may decrease.

[0007] In view of the above problems, the present invention aims to provide a polypropylene-based resin expanded bead having through holes, which can be molded into an expanded bead molding having voids and excellent rigidity, can be molded in a mold at a low steam pressure, and can be molded in a mold at a wide pressure range even at a high steam pressure that would conventionally cause a decrease in porosity. Another object of the present invention is to provide a polypropylene-based resin expanded bead molding having excellent rigidity and high porosity, which is obtained by molding the expanded beads in a mold. [Means for solving the problem]

[0008] According to the present invention, there are provided expanded beads having through holes and expanded bead moldings having interconnected voids, as described below. [1] A foamed bead having a through hole, the expanded beads have an expanded core layer having the through holes formed therein and made of a polypropylene-based resin composition, and a coating layer covering the expanded core layer and made of a polyolefin-based resin, The polypropylene-based resin composition comprises 70 to 97% by weight of a propylene-based resin PP1 having a melting point of more than 140°C and not more than 150°C, and 3 to 30% by weight of a polypropylene-based resin PP2 having a melting point of 145°C or more and 160°C or less (provided that the total of the resins PP1 and PP2 is 100% by weight); the difference between the melting point of the polypropylene-based resin PP2 and the melting point of the polypropylene-based resin PP1 [(melting point of PP2) - (melting point of PP1)] is 5°C or more and less than 15°C; the expanded beads have a crystal structure that gives a first DSC curve when measured by heat flux differential scanning calorimetry in which the expanded beads are heated from 30°C to 200°C at a heating rate of 10°C / min, The first DSC curve has a main endothermic peak specific to the polypropylene-based resin composition and a high-temperature endothermic peak located on the higher temperature side than the main endothermic peak, The expanded polypropylene resin particles have a calorific value of the higher temperature endothermic peak of 12 to 20 J / g, and a ratio of the calorific value of the main endothermic peak to the calorific value of the higher temperature endothermic peak of 3.5 or more. [2] The polypropylene-based resin expanded particles according to the above [1], wherein the polypropylene-based resin PP1 has a melting point of more than 140°C and not more than 145°C, and the polypropylene-based resin PP2 has a melting point of 150°C or more and 155°C or less. [3] The expanded polypropylene resin particles according to the above [1] or [2], wherein the polypropylene resin PP2 has a melt flow rate (MFR) of 2 to 18 g / 10 min at 230° C. under a load of 2.16 kg. [4] The expanded polypropylene resin particles according to any one of the above [1] to [3], wherein the polypropylene resin PP1 and the polypropylene resin PP2 are each obtained by polymerization in the presence of a Ziegler-Natta polymerization catalyst. [5] The bulk density of the foamed particles is 15 to 50 kg / m 3 The expanded polypropylene resin particles according to any one of the above [1] to [4], [6] The expanded polypropylene resin particles according to any one of the above [1] to [5], having an average outer diameter D (mm), an average pore diameter d (mm) of the through holes, and an average wall thickness t (mm) defined as (Dd) / 2, wherein t is 0.8 to 2 mm, and t / d is 0.4 to 1. [7] A polypropylene-based resin expanded bead molding comprising a large number of expanded beads according to any one of the above [1] to [6] fused to one another, wherein the expanded bead molding has interconnected voids and a porosity of 20% or more. Effect of the Invention

[0009] According to the present invention, there is provided expanded polypropylene resin beads which are excellent in rigidity and can be molded in a mold to produce an expanded bead molding having a high porosity within a wider pressure range than conventionally possible. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing an example of the expanded beads of the present invention. [Figure 2(a)] FIG. 2 is a schematic cross-sectional view showing one example of a foamed core layer of the present invention. [Figure 2(b)] FIG. 4 is a schematic cross-sectional view showing another example of a foam core layer. [Figure 2(c)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 2(d)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 2(e)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 2(f)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 2(g)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 2(h)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 3(a)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 3(b)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 3(c)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 3(d)] FIG. 2 is a schematic cross-sectional view showing a further example of a foam core layer. [Figure 4] 1 is a schematic diagram showing an example of the surface state of an expanded bead molding of the present invention having interconnected voids. FIG. [Diagram 5] FIG. 2 is a schematic diagram showing an example of a first DSC curve in heat flux differential scanning calorimetry of the expanded beads of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The polypropylene resin expanded beads having through holes and the polypropylene resin expanded bead molded article having interconnected voids (hereinafter, simply referred to as expanded bead molded article or molded article) of the present invention will be described in detail below. In this specification, "A to B" representing a numerical range is synonymous with "A or more and B or less" and represents a numerical range including A and B, which are the end points of the numerical range. In this specification and claims, the singular form (a, an, the) includes the plural form unless the context clearly indicates otherwise. Thus, for example, an expanded bead includes two or more expanded beads. Unless otherwise specified in this specification or clearly contradictory in the context, the singular and plural forms are included. The polypropylene resin expanded beads having through holes of the present invention (hereinafter, simply referred to as expanded beads) are multi-layer expanded beads having an expanded core layer and a coating layer that covers the expanded core layer. An intermediate layer may be provided between the expanded core layer and the coating layer, but it is preferable not to provide an intermediate layer because it is desired to reduce the thickness of the coating layer for reasons described below. It is preferable that the expanded beads are non-crosslinked because the expanded beads are excellent in recyclability, productivity, etc.

[0012] 1 is a schematic diagram showing an example of a polypropylene resin expanded bead having a cylindrical foamed core layer and a coating layer covering the foamed core layer. The expanded bead, designated by reference numeral 2, is a generally cylindrical foam having a through hole 4. The expanded bead 2 includes an expanded core layer 3 having the through hole 4 formed therein, and a coating layer 5 covering the expanded core layer 3.

[0013] The covering layer 5 may be foamed or not. However, in order to achieve the purpose of increasing the rigidity of the expanded bead molding, it is preferable that the covering layer 5 is not foamed. Here, "not foamed" refers not only to the case where no air bubbles are present in the covering layer (including the case where air bubbles once formed are melted and destroyed and disappear), but also to the case where there are only a few very small air bubbles and the layer is substantially not foamed. Furthermore, "covering the foamed core layer 3" does not necessarily mean that the entire foamed core layer 3 is covered, and there may be a part where the foamed core layer 3 is exposed. Since this can more reliably improve the fusion property of the expanded beads, it is preferable that the entire periphery of the side surface side of the cylindrical foamed core layer 3 is covered. All or most of both end faces of the foamed core layer 3 that form the openings of the through holes 4 are not covered with the covering layer 5.

[0014] Next, the resin constituting the foamed core layer 3 will be described. The foamed core layer is composed of a polypropylene-based resin composition (a) (hereinafter, also simply referred to as resin composition (a)). In this specification, the polypropylene resin refers to a resin having a propylene-derived structural unit as the main structural unit. Here, the main structural unit means that the content of the propylene component unit in the polymer exceeds 50% by weight, preferably 80% by weight or more, and more preferably 90% by weight or more.

[0015] The polypropylene-based resin may be a propylene homopolymer or a propylene-based copolymer containing a structural unit derived from propylene and other structural units. Examples of the propylene-based copolymer include copolymers of propylene and ethylene and / or an α-olefin having 4 to 20 carbon atoms, specifically, copolymers of propylene and one or more comonomers selected from ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 4-methyl-1-butene, 4-methyl-1-pentene, etc. Furthermore, the propylene-based copolymer may be a binary copolymer such as a propylene-ethylene random copolymer or a propylene-1-butene random copolymer, or a ternary copolymer such as a propylene-ethylene-butene random copolymer. Expanded beads containing these random copolymers as the main component have excellent secondary foaming properties during molding in a mold and also have excellent mechanical properties. The total content of comonomer components such as ethylene and / or an α-olefin having 4 to 20 carbon atoms in the propylene-based copolymer is preferably 25% by weight or less, and more preferably 10% by weight or less.

[0016] The polypropylene-based resin composition (a) constituting the foamed core layer of the present invention contains, as main components, a polypropylene-based resin PP1 (hereinafter, simply referred to as resin PP1 or PP1) and a polypropylene-based resin PP2 (hereinafter, simply referred to as resin PP2 or PP2), which satisfy the following requirements (i) and (ii): (i) The polypropylene-based resin composition (a) comprises 70% to 97% by weight of a propylene-based resin PP1 having a melting point MP1 exceeding 140°C and not exceeding 150°C, and 3% to 30% by weight of a polypropylene-based resin PP2 having a melting point MP2 of 145°C or higher and 160°C or lower (however, the sum of resin PP1 and resin PP2 is 100% by weight). (ii) The difference (MP2 - MP1) between the melting point MP2 of the resin PP2 and the melting point MP1 of the resin PP1 is 5°C or more and less than 15°C. That is, MP1 and MP2 satisfy the following relationship: 5℃ ≦ MP2 - MP1 < 15℃ The meaning and effect of requirements (i) and (ii) will be explained in more detail later.

[0017] In this specification, the term "containing resins PP1 and PP2 as the main components" means that the total amount of resins PP1 and PP2 in resin composition (a) exceeds 50% by weight. The total amount of resins PP1 and PP2 in resin composition (a) is preferably 80% by weight or more, and more preferably 90% by weight or more.

[0018] Among the above-mentioned polypropylene resins, the following polypropylene resins are preferred as resins PP1 and PP2.

[0019] Resin PP1 is preferably a propylene-based random copolymer, and more preferably a propylene-ethylene random copolymer. In consideration of the melting point and foamability of resin PP1, the total content of comonomer components in resin PP1 is preferably 0.5% by weight or more, more preferably 1.0% by weight or more, and even more preferably 1.5% by weight or more. For the same reason, the total content of comonomer components in resin PP1 is preferably 10% by weight or less, more preferably 8.0% by weight or less, and even more preferably 5.0% by weight or less.

[0020] Resin PP2 is preferably a propylene-based random copolymer, since it has excellent compatibility with resin PP1 and is expected to improve the mechanical properties and secondary foaming properties of the resulting expanded beads, and is particularly preferably a random copolymer of propylene and ethylene and / or 1-butene. In consideration of the melting point and mechanical properties of resin PP2, the total content of comonomer components in resin PP2 is preferably 0.3% by weight or more, more preferably 0.5% by weight or more, and even more preferably 0.8% by weight or more. For the same reason, the total content of comonomer components in resin PP2 is preferably 5.0% by weight or less, more preferably 3.0% by weight or less, and even more preferably 1.0% by weight or less. In addition, in order to more reliably achieve the intended effect of the present invention, which is to enable in-mold molding of a molded body having excellent rigidity and high porosity over a wide pressure range, it is preferable that the total content of comonomer components in resin PP2 is lower than the total content of comonomer components in resin PP1.

[0021] Resin PP1 and resin PP2 used in the present invention are preferably polypropylene resins obtained by polymerization in the presence of a Ziegler-Natta polymerization catalyst. Polypropylene resins produced using a Ziegler-Natta polymerization catalyst tend to have a broader molecular weight distribution than polypropylene resins produced using a metallocene catalyst. Therefore, expanded beads made of polypropylene resins polymerized using a Ziegler-Natta catalyst tend to have better secondary foaming properties than expanded beads made of polypropylene resins polymerized using a metallocene polymerization catalyst, and tend to have better secondary foaming properties under a wide range of vapor pressures from low pressure to high pressure. The Ziegler-Natta polymerization catalyst is an organometallic complex whose core element is titanium, aluminum, magnesium, etc., and which is partially or completely modified with alkyl groups.

[0022] As long as the effects of the present invention are achieved, the polypropylene resin composition (a) may contain other resins, polymers such as rubber and elastomers, additives, and the like. Examples of other resin components include ethylene-based resins such as high-density polyethylene, low-density polyethylene, linear low-density polyethylene, linear very low-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, and ethylene-methacrylic acid copolymer, styrene-based resins such as polystyrene and styrene-maleic anhydride copolymer, and polyamide-based resins. Examples of rubbers and elastomers include rubbers such as ethylene-propylene rubber, ethylene-1-butene rubber, propylene-1-butene rubber, ethylene-propylene-diene rubber, isoprene rubber, neoprene rubber, and nitrile rubber, and thermoplastic elastomers such as styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated styrene-butadiene-styrene block copolymer, and hydrogenated styrene-isoprene-styrene block copolymer.

[0023] These polymers can be used in combination of two or more kinds. When the resin composition (a) contains the other polymer components, the total amount thereof is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, even more preferably 10 parts by weight or less, and particularly preferably 5 parts by weight or less, based on 100 parts by weight of the entire resin composition (a).

[0024] The additives include various additives such as bubble regulators such as zinc borate, antistatic agents, flame retardants, conductivity imparting agents, lubricants, antioxidants, UV absorbers, metal deactivators, pigments, dyes, crystal nucleating agents, and inorganic fillers, which can be included in the resin composition (a) as desired. The amount of the additive varies strictly depending on the purpose of its addition, but is preferably 0.5 to 25 parts by weight, more preferably 1 to 15 parts by weight, and even more preferably 3 to 15 parts by weight, relative to 100 parts by weight of the total of the resins PP1 and PP2.

[0025] The melt flow rate (MFR) of the resin PP1 is preferably 1 g / 10 min or more, more preferably 3 g / 10 min or more, and even more preferably 6 g / 10 min, because this provides an excellent balance of foamability, moldability, mechanical properties, and the like, and is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, and even more preferably 15 g / 10 min or less.

[0026] The melt flow rate (MFR) of the resin PP2 is preferably 2 g / 10 min or more, more preferably 3 g / 10 min or more, and even more preferably 5 g / 10 min or more, because it has an excellent effect of improving foamability over a wide range of pressures and an excellent effect of improving mechanical properties, and is preferably 18 g / 10 min or less, more preferably 15 g / 10 min or less, and even more preferably 12 g / 10 min or less.

[0027] In this specification, the MFR of the polypropylene resins PP1 and PP2 and the polypropylene resin composition (a) is a value measured under test condition M (temperature 230°C, load 2.16 kg) of JIS K7210:2014. The MFR of the polyethylene resin is a value measured under test condition D (temperature 190°C, load 2.16 kg) of JIS K7210:2014.

[0028] The expanded beads having through holes of the present invention have a specific crystal structure that satisfies the following requirements (1) and (2).

[0029] That is, the expanded beads have a crystal structure that gives a first DSC curve when measured by heat flux differential scanning calorimetry in which an expanded bead sample is heated from 30°C to 200°C at a heating rate of 10°C / min, and the first DSC curve has a main endothermic peak specific to the polypropylene resin composition (a) and a high-temperature endothermic peak located on the high-temperature side of the main endothermic peak, wherein (1) The calorific value of the high-temperature endothermic peak (high-temperature peak calorific value) ΔHh is 12 to 20 J / g, (2) The ratio ΔHm / ΔHh of the calorific value of the intrinsic main peak (intrinsic peak calorific value) ΔHm to the calorific value ΔHh of the higher temperature endothermic peak is 3.5 or more.

[0030] The expanded beads of the present invention have an expanded core layer composed of the resin composition (a) containing the polypropylene-based resin PP1 and the polypropylene-based resin PP2 as main components, and the crystal structure of the expanded beads satisfies the requirements (1) and (2), so that the expanded beads have excellent fusibility and secondary foaming properties, and can be molded in a good expanded bead molding even at a low vapor pressure. Even when molding in a mold at a high vapor pressure that would have reduced the void ratio in the past, the reduction in the void ratio can be suppressed. Furthermore, the obtained expanded bead molding has excellent rigidity. The meaning and effects of requirements (1) and (2) will be explained in more detail later.

[0031] Next, the meanings and effects of the above-mentioned requirements (i) and (ii) for the expanded beads will be explained in detail. The polypropylene resin composition (a) constituting the foamed core layer of the present invention is (i) a mixed resin having as a main component a low-melting-point resin PP1 having a melting point MP1 of more than 140° C. and not more than 150° C., and as a secondary component a high-melting-point resin PP2 having a melting point MP2 of 145° C. or more and not more than 160° C. In addition, (ii) the difference (MP2)-(MP1) between the melting point MP2 of the resin PP2 and the melting point MP1 of the resin PP1 is 5° C. or more and less than 15° C.

[0032] Since the resin composition (a) constituting the expanded beads of the present invention contains the high-melting point resin PP2 as a secondary component, the resulting expanded bead molding has high rigidity, such as that required for automobile seat members.

[0033] In addition, since the resin composition (a) contains the resin PP1 having a low melting point as a main component, the expanded beads of the present invention can be molded in a mold at a low vapor pressure. Furthermore, although the expanded beads contain the resin PP2 having a higher melting point than the resin PP1 as a secondary component, the expanded beads can be molded in a mold at a vapor pressure that is the same as or lower than the vapor pressure required for molding the resin PP1 alone. The reason for this is believed to be as follows. The expanded beads of the present invention have an expanded core layer made of a mixed resin in which a low-melting-point resin PP1 is mixed with a resin PP2 having a melting point higher than that of the resin PP1 by a certain amount in a specific ratio, and the ratio ΔHm / ΔHh of the intrinsic peak heat quantity ΔHm to the high-temperature peak heat quantity ΔHh in the first DSC curve of the expanded beads is likely to be large. That is, since the expanded beads of the present invention contain many low-potential crystals that show a peak on the low-temperature side, the low-potential crystals can contribute to expansion even in in-mold molding at a low vapor pressure, and as a result, the expanded beads exhibit improved secondary expandability.

[0034] In addition, since the expanded beads of the present invention are a mixture of the low-melting resin PP1 and the high-melting resin PP2, whose melting points are within the above range, it is considered that, for example, it is easy to set the expansion temperature high, and it is easy to obtain expanded beads having a crystal structure with a large ratio of the heat quantity of the main endothermic peak. The crystal structure and setting the expansion temperature high will be described later.

[0035] In addition, in the case of the expanded beads of the present invention, even when molding is performed in a mold at a high steam pressure, the porosity of the resulting expanded bead molding is prevented from decreasing, and as a result, the range of steam pressures at which a molding with a high porosity can be molded is expanded to the high steam pressure side. The reason why the expanded beads prevent the porosity of the expanded bead molding from decreasing during high pressure molding is considered to be as follows. It is generally known that the porosity of a multilayer foamed bead molding decreases as the molding pressure increases. This is for the following reasons. In molding at low steam pressure, the coating layer melts and heat-seals before the secondary expansion of the core layer is complete (while the through-hole diameter is adequately maintained), so a molding with a high porosity can be easily obtained. In contrast, in molding at high steam pressure, the secondary expansion of the core layer progresses, and the through-holes are fused in a state where they are crushed, so the porosity is likely to decrease. The expanded beads of the present invention are made of a resin mixture in which resin PP1 and resin PP2, both of which have a melting point in a specific range, are mixed in a specific ratio, and resin PP2 with a high melting point is used as a secondary component, and a polypropylene-based resin with a high melting point of more than 140°C and not more than 150°C is used as the main component of the low-melting-point resin PP1, so that the melting point of the entire core layer can be adjusted to a high value. Therefore, the appropriate molding steam pressure range of the core layer (the range of molding steam pressure for secondary foaming) can be expanded to the higher pressure side. As a result, it is considered that a molded body with a high porosity can be molded in a mold over a wide range of vapor pressures from low to high.

[0036] The melting point MP1 of the polypropylene resin PP1 is more than 140°C and is not more than 150°C. If the melting point MP1 is more than 150°C, the steam pressure required for in-mold molding of the expanded beads may be high. For this reason, the melting point MP1 is preferably 148°C or less, more preferably 146°C or less, even more preferably 145°C or less, and particularly preferably 144°C or less. If the melting point MP1 is 140°C or less, the porosity of the molded body may decrease when the steam pressure during in-mold molding is increased. For this reason, the melting point MP1 is preferably 141°C or more, and more preferably 142°C or more.

[0037] The melting point MP2 of the polypropylene resin PP2 is 145°C or more and 160°C or less. If the melting point MP2 is more than 160°C, it becomes difficult to adjust the high-temperature peak calorific value of the expanded beads to the range of the requirement (1), and the moldability of the expanded beads and the rigidity of the obtained molded body may decrease. For such reasons, the melting point MP2 is preferably 158°C or less, more preferably 156°C or less, even more preferably 155°C or less, and particularly preferably 153°C or less. If the melting point MP2 is less than 145°C, the rigidity of the obtained molded body may decrease. In addition, it becomes difficult to control the ratio ΔHm / ΔHh of the intrinsic peak calorific value ΔHm to the high-temperature peak calorific value ΔHh of the expanded beads, and the effect of reducing the molding pressure may not be sufficiently obtained. For such reasons, the melting point MP2 is preferably 146°C or more, more preferably 148°C or more, even more preferably 150°C or more, and particularly preferably 151°C or more.

[0038] In addition, the difference (MP2-MP1) between the melting point MP2 of resin PP2 and the melting point MP1 of resin PP1 is 5°C or more and less than 15°C. If the melting point difference is too small, the range of vapor pressures capable of molding a molded body having a high porosity may be narrowed. For this reason, the melting point difference (MP2-MP1) is preferably 6°C or more, more preferably 8°C or more. If the melting point difference is too large, it is difficult to control the foamability, and the intended effect of the present application may not be achieved. For this reason, the melting point difference (MP2-MP1) is preferably 13°C or less, more preferably 12°C or less.

[0039] The melting points MP1 and MP2 can be measured in accordance with JIS K7121:2012. Specifically, a resin piece is used as a sample, and is heated from 30°C to 200°C at a heating rate of 10°C / min, cooled to 30°C at a cooling rate of 10°C / min, and then heated again from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve. The temperature at the apex of the melting peak in the obtained DSC curve is taken as the melting point. When two or more melting peaks appear, the temperature at the apex of the melting peak with the largest area is taken as the melting point.

[0040] In the resin composition (a), the content of resin PP1 is 70% by weight to 97% by weight, and the content of resin PP2 is 3% by weight to 30% by weight (the total amount of resin PP1 and resin PP2 is 100% by weight). When the contents of resin PP1 and resin PP2 are within this range, an expanded bead molding having high porosity and excellent rigidity can be obtained by in-mold molding over a wide range of vapor pressure. If the content of the resin PP2 is too low, the desired effect of improving the rigidity may not be obtained, whereas if the content of the resin PP2 is too high, the properties of the resin PP2, which has a high melting point, are significantly reflected, and the moldability at the low vapor pressure side may decrease. For these reasons, the lower limit of the content of the resin PP1 is preferably 75% by weight, more preferably 80% by weight, and even more preferably 85% by weight. The upper limit is preferably 95% by weight, more preferably 93% by weight, and even more preferably 90% by weight. On the other hand, the lower limit of the content of the resin PP2 is preferably 5% by weight, more preferably 7% by weight, and even more preferably 10% by weight. The upper limit is preferably 25% by weight, more preferably 20% by weight, and even more preferably 15% by weight.

[0041] Next, the DSC curve of the expanded beads of the present invention will be described. The first DSC curve of the expanded beads obtained under the specific DSC measurement conditions has a main endothermic peak specific to the polypropylene resin composition (a) and a high-temperature side endothermic peak located on the high-temperature side of the main endothermic peak, and satisfies the following requirements (1) and (2). (1) The calorific value ΔHh of the endothermic peak on the high temperature side is 12 to 20 J / g, (2) The ratio ΔHm / ΔHh of the calorific value ΔHm of the intrinsic main endothermic peak to the calorific value ΔHh of the higher temperature endothermic peak is 3.5 or more.

[0042] When the calorific value ΔHh of the high-temperature peak is within the above range, the expanded beads have excellent moldability, and the rigidity of the resulting expanded bead molded article is improved. For these reasons, the calorific value ΔHh is preferably 13 to 18 J / g.

[0043] Furthermore, when the ratio ΔHm / ΔHh is 3.5 or more, the number of crystals (low potential crystals) that show a peak on the low temperature side increases, and secondary foaming properties during in-mold molding at low vapor pressure are particularly improved. For these reasons, the ratio ΔHm / ΔHh is preferably 3.6 or more, more preferably 3.7 or more. The upper limit of the ratio ΔHm / ΔHh is about 4.2. The ratio ΔHm / ΔHh can be controlled by adjusting the foaming temperature during the production of the expanded beads, the foaming agent impregnation pressure, or the temperature conditions and retention time of the crystallization process. Since the expanded beads of the present invention are a mixture of a low-melting resin PP1 and a high-melting resin PP2, whose melting points are within the range specified in (i) above, it is easy to set the foaming temperature high, for example, and expanded beads having a crystal structure with a large ratio ΔHm / ΔHh can be easily obtained.

[0044] The high-temperature peak calorific value ΔHh and the intrinsic peak calorific value ΔHm (low-temperature peak calorific value) of the expanded beads are measured by a measurement method conforming to JIS K7122:2012 as follows: 1 to 3 mg of the expanded beads are sampled, and the temperature is increased from 30° C. to 200° C. at a rate of 10° C. / min using a heat flux differential scanning calorimeter. An example of the first DSC curve obtained by such measurement is shown in FIG. 6.

[0045] In the DSC curve of FIG. 6, a main endothermic peak A (intrinsic peak A) appears on the low temperature side, and a high-temperature peak B appears on the high-temperature side of the inherent peak A. The heat quantities of inherent peak A and high-temperature peak B correspond to the respective peak areas, and specifically can be calculated as follows. A straight line (α-β) is drawn connecting point α corresponding to 80°C on the DSC curve and point β on the DSC curve corresponding to the melting end temperature T of the expanded beads. The melting end temperature T refers to the intersection point between the DSC curve on the high temperature side of high temperature peak B and the high temperature side baseline. Next, a straight line parallel to the vertical axis of the graph is drawn from point γ on the DSC curve which corresponds to the valley between the resin intrinsic peak A and high temperature peak B, and the point where this line intersects with the straight line (α-β) is designated as σ. The area of ​​high-temperature peak B is the area surrounded by the curve of the high-temperature peak B part of the DSC curve, the line segment (σ-β), and the line segment (γ-σ), and this is the high-temperature peak heat quantity ΔHh. The area of ​​the intrinsic peak is the area surrounded by the curve of the resin intrinsic peak A part of the DSC curve, the line segment (α-β), and the line segment (γ-σ), and this is the intrinsic peak heat quantity ΔHm.

[0046] The high-temperature peak is observed in the first DSC curve obtained by heating the expanded bead sample from 30°C to 200°C at 10°C / min as described above, but does not appear in the second DSC curve obtained by subsequently lowering the temperature from 200°C to 30°C at 10°C / min after the first DSC curve is obtained and then raising the temperature to 200°C at 10°C / min again. Therefore, whether or not a high-temperature peak exists in the first DSC curve can be easily determined by performing a second DSC measurement following the first DSC measurement to obtain a second DSC curve. That is, an endothermic peak in the first DSC curve that appears in the first DSC curve but does not exist in the second DSC curve is recognized as a high-temperature peak.

[0047] In order to further improve the foamability, moldability, mechanical strength, etc., the heat of fusion of the polypropylene-based resin PP1 is preferably 30 to 100 J / g, more preferably 40 to 80 J / g, and even more preferably 50 to 75 J / g.

[0048] The heat of fusion of the resin PP2 is preferably higher than that of the resin PP1. It is considered that the heat of fusion of the resin PP2 is higher than that of the resin PP1, and thus the expanded beads can be molded in a mold at a lower vapor pressure. For this reason, the heat of fusion of the resin PP2 is preferably 40 to 120 J / g, more preferably 60 to 100 J / g, and even more preferably 75 to 90 J / g. The heat of fusion of resin PP1 and resin PP2 is measured using a heat flux differential scanning calorimeter with a resin piece as a sample based on JIS K7122: 2012. When multiple melting peaks appear on the DSC curve, the total area of ​​the multiple melting peaks is regarded as the heat of fusion.

[0049] The flexural modulus of the resin PP1 is preferably 600 to 1200 MPa, and more preferably 800 to 1000 MPa, in order to provide an excellent balance between foamability, moldability, mechanical properties, and the like. The flexural modulus of the resin PP2 is preferably from 1000 to 1800 MPa, and more preferably from 1200 to 1500 MPa, because this has a greater effect of improving mechanical properties. The flexural modulus of resin PP1 and resin PP2 can be measured in accordance with JIS K7171:2008.

[0050] Next, the coating layer of the expanded beads will be described. The covering layer is a layer that covers the core layer, and is made of a polyolefin resin (b). The polyolefin resin (b) refers to a resin having as its main constituent units constituent units derived from α-olefins such as ethylene, propylene, 1-butene, etc. Here, the main constituent units refer to constituent units whose content in the polymer exceeds 50% by weight, and preferably exceeds 80% by weight. Examples of the polyolefin resin (b) include the following (b1), (b2), and (b3):

[0051] (b1) Ethylene or α-olefin homopolymers, for example, ethylene homopolymers, propylene homopolymers, etc.

[0052] (b2) Copolymers of two or more monomer components selected from ethylene and α-olefins are included. The copolymers preferably contain at least one of ethylene-derived structural units and propylene-derived structural units. Examples of ethylene copolymers include ethylene-1-pentene copolymers, ethylene-1-hexene copolymers, and ethylene-4-methyl-1-pentene copolymers. Examples of propylene copolymers include propylene-ethylene copolymers, propylene-1-butene copolymers, and propylene-ethylene-1-butene copolymers. These copolymers may be block copolymers, random copolymers, or graft copolymers.

[0053] (b3) Copolymers of ethylene and / or α-olefin and other monomer components such as styrene. In the copolymer, the structural units derived from ethylene and / or α-olefin are preferably structural units derived from ethylene or / and structural units derived from propylene. Examples include ethylene-styrene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl methacrylate copolymers, and ethylene-methacrylic acid copolymers.

[0054] The resin constituting the coating layer in the present invention is preferably a polyethylene-based resin because it has excellent fusion properties with the expanded beads. Here, the polyethylene-based resin means the polymer or copolymer of (b1) to (b3) above, in which the main constituent unit is an ethylene-derived constituent unit. Among them, the copolymer of (b2) is preferred, and specifically, linear low-density polyethylene and linear very low-density polyethylene are more preferred.

[0055] The polyolefin resin (b) may be crystalline or amorphous. Whether resin (b) is crystalline or amorphous can be confirmed by a DSC curve obtained by performing heat flux differential scanning calorimetry using resin (b) as a sample. If resin (b) is crystalline, an endothermic peak appears on the DSC curve, and if resin (b) is amorphous, no endothermic peak appears on the DSC curve.

[0056] When the polyolefin resin (b) is a crystalline polyolefin resin, the resin (b) has a melting point (TmB) lower than the melting point (TmA) of the polypropylene resin composition (a), and the difference between the melting point (TmA) and the melting point (TmB) [TmA-TmB] is preferably more than 0°C and 80°C or less. When this condition is satisfied, the expanded beads have excellent fusibility. For this reason, the difference [TmA-TmB] is more preferably 5°C or more and 60°C or less, even more preferably 7°C or more and 50°C or less, and particularly preferably 10°C or more and 40°C or less.

[0057] In addition, when the olefin resin (b) is an amorphous polyolefin resin, the resin (b) has a softening point (TsB) lower than the melting point (TmA) of the polypropylene resin composition (a), and the difference between the melting point (TmA) and the softening point (TsB) [TmA-TsB] is preferably more than 0°C and 100°C or less. When this condition is satisfied, the expanded beads have excellent fusibility. For this reason, the difference [TmA-TsB] is more preferably 10°C or more and 80°C or less, even more preferably 15°C or more and 75°C or less, and particularly preferably 20°C or more and 70°C or less.

[0058] Resin (b) can be polymerized using various polymerization catalysts. Examples of the polymerization catalyst include Ziegler-Natta polymerization catalysts and metallocene polymerization catalysts. Among these polymerization catalysts, metallocene polymerization catalysts are preferred. When a metallocene polymerization catalyst is used, an olefin resin with a low melting point or low softening point and excellent fusibility can be obtained.

[0059] The resin (b) constituting the coating layer of the expanded beads of the present invention may contain other polymer components that may be contained in the above-mentioned resin composition (a) within the range in which the effects of the present invention are achieved. The total content of other polymer components in the coating layer is preferably approximately 20 parts by weight or less, more preferably 15 parts by weight or less, even more preferably 10 parts by weight or less, and particularly preferably 5 parts by weight or less, per 100 parts by weight of resin (b).

[0060] Resin (b) may contain various additives. The additives may be the same as those contained in resin (a). The content of the additives may vary depending on the purpose of the additives, but is preferably about 25 parts by weight or less, more preferably 20 parts by weight or less, even more preferably 15 parts by weight or less, and particularly preferably 8 parts by weight or less, per 100 parts by weight of resin (b). Resin (b) may contain additives without inhibiting the foaming property.

[0061] The weight ratio (wt%) of the foamed core layer to the coating layer is preferably 99.5:0.5 to 75:25, more preferably 98:2 to 80:20, and further preferably 96:4 to 90:10. When the weight ratio of the foamed core layer to the coating layer is within this range, the effect of improving the fusion property by the coating layer is further improved, and the rigidity of the obtained foamed bead molding is further improved.

[0062] In the expanded beads of the present invention, the thickness of the coating layer is preferably 1 μm to 50 μm, more preferably 2 μm to 20 μm, and further preferably 3 μm to 10 μm. If the thickness of the coating layer is within this range, the fusion property during in-mold molding is improved, and the rigidity of the obtained expanded bead molding is improved.

[0063] Next, the shape and dimensions of the expanded beads of the present invention will be described. As shown in FIG. 1, the expanded beads 2 of the present invention have an expanded core layer 3 having a through hole 4 and a covering layer 5 covering the expanded core layer 3, and the overall shape is usually cylindrical. The expanded core layer 3 can be embodied in various forms 3a to 3m, for example, as shown in FIG. 2(a) to FIG. 2(h) and FIG. 3(a) to FIG. 3(d). Usually, the expanded core layer 3 is an expanded core layer 3a having a circular cross section, as shown in FIG. 2(a). If necessary, a core layer 3b having a triangular cross section, as shown in FIG. 2(b), a core layer 3c having a hexagonal cross section, as shown in FIG. 2(c), a core layer 3d having a bisected circular cross section, as shown in FIG. 2(d), a core layer 3e, 3f having a cross section in the form of a plurality of circles joined together, as shown in FIG. 2(e) and 2(f), a core layer 3g having a circular cross section with a portion missing, as shown in FIG. 2(g), and a core layer 3h having a rectangular cross section with a portion missing, as shown in FIG. 2(h), can be adopted. Furthermore, as shown in FIG. 3(a), a core layer 3i having a cross section in the shape of a circle with three limbs e extending from the circumference, as shown in FIG. 3(b), a core layer 3j having a cross section in the shape of a triangle with three limbs e extending from each side, as shown in FIG. 3(c), a core layer 3k having a cross section in the shape of a circle with six limbs e extending from the circumference, as shown in FIG. 3(c), and a core layer 3m having a cross section in the shape of a triangle with a total of six limbs e extending from its vertices and each side, as shown in FIG. 3(d), can also be applied. The cross-sectional shape of the core layer 3 is not limited to the above cross-sectional shape, and may be an irregular cross-sectional shape. Similarly, the cross-sectional shape of the through-hole 4 of the foamed core layer 3 is usually a circle, but may be various shapes as shown in FIG. 2(a) to FIG. 2(h) and FIG. 3(a) to FIG. 3(d) as necessary, or may be an irregular shape.

[0064] The average pore diameter d of the through-holes of the expanded beads of the present invention is preferably 1 to 3 mm. If the average pore diameter d is within this range, it becomes easier to adjust the porosity of the expanded bead molding to a desired range. For this reason, the average pore diameter d is more preferably 1.2 to 2.5 mm. The average outer diameter D of the expanded beads is preferably 1.5 to 7 mm. If the average outer diameter D is within this range, it is possible to obtain a good expanded bead molding having excellent filling properties. For this reason, the average outer diameter D of the expanded beads is more preferably 2 to 6 mm, and further preferably 3 to 5 mm.

[0065] The average pore diameter d of the through holes of the expanded beads is determined as follows. First, the expanded beads are cut perpendicularly to the penetration direction of the through holes at the position where the area of ​​the cut surface is maximum. A photograph of the cut surface of the expanded beads obtained is taken, the area of ​​the through holes in the photograph (i.e., the cross-sectional area of ​​the through holes) is determined, and the diameter of an imaginary perfect circle having the same area as that area is calculated, and this value is the pore diameter of the through holes of the expanded beads. The above measurement is performed on 50 expanded beads, and the arithmetic average value is the average pore diameter d of the expanded beads.

[0066] The average outer diameter D of an expanded bead is determined as follows. First, an expanded bead is cut perpendicularly to the penetration direction of the through holes at a position where the area of ​​the cut surface is maximum. A photograph of the resulting cut surface of the expanded bead is taken, and the area of ​​the expanded bead in the photograph (i.e., the cross-sectional area of ​​the expanded bead including the cross-sectional area of ​​the through holes) is determined. The diameter of an imaginary perfect circle having the same area as that area is calculated, and this value is the outer diameter of the expanded bead. The above measurement is performed on 50 randomly selected expanded beads, and the arithmetic average value thereof is the average outer diameter D of the expanded beads.

[0067] The average wall thickness t of the expanded beads of the present invention is preferably 0.8 to 2 mm. If the average wall thickness t is within this range, the expanded beads are thick, so that the expanded beads are less likely to be crushed by external forces and the expanded beads located on the surface of the molded article are less likely to be damaged. For these reasons, the average wall thickness t of the expanded beads 2 is more preferably 0.9 to 1.5 mm, and even more preferably 1.0 to 1.4 mm. Conventionally, in the case of thick-walled expanded beads, the pore size of the through holes tends to be small, making it difficult to obtain a molded article with a high porosity. According to the expanded beads of the present invention, even if the expanded beads are thick, a molded article with a high porosity can be obtained over a wide range of molding pressures. The average wall thickness t of the expanded beads is determined by the following formula. t=(Dd) / 2 where d and D are as previously defined.

[0068] Furthermore, the ratio t / d of the average wall thickness t to the average hole diameter d of the through holes is preferably 0.4 to 1, and more preferably 0.6 to 0.9. When the ratio t / d is within this range, the difference between the compression characteristics in the penetrating direction of the through holes of the expanded beads and the direction perpendicular to the through holes becomes small, and an expanded bead molding having well-balanced compression characteristics as a whole can be obtained.

[0069] The average length L of the expanded beads is preferably 2 to 7 mm. The average length L of the expanded beads is determined as follows. 50 expanded beads are randomly selected, and the maximum length of the through-hole of each expanded bead in the penetration direction is measured with a vernier caliper. The average length L is the arithmetic average of the 50 measured values ​​obtained. The ratio L / D of the average length L to the average outer diameter D of the expanded beads 2 is preferably 0.5 to 2, and more preferably 1 to 1.5, in order to provide excellent filling ability into a mold during in-mold molding and excellent fusion between the expanded beads.

[0070] In addition, even when the expanded beads form an expanded bead molding, the average pore size d, average outer diameter D, and average wall thickness t of the expanded beads can be determined in the same manner as the measurement method for the expanded beads. Specifically, the expanded beads forming the expanded bead molding are sampled, and a photograph of a cross section perpendicular to the through holes is taken, and the measurements can be performed using image analysis software or the like.

[0071] Next, the bulk density and average cell diameter of the expanded beads of the present invention will be described. In the present invention, since it is easy to achieve both light weight and rigidity of the molded product, the bulk density of the expanded beads is 15 to 50 kg / m 3 is preferably 20 to 40 kg / m 3 It is more preferable that:

[0072] The bulk density is measured as follows. A number of foamed beads are randomly taken from the group of foamed beads and placed in a measuring cylinder with a volume of 1 L. While removing static electricity, a large number of foamed beads are placed in a natural pile-up state up to the 1 L mark. Next, the weight of the foamed beads placed is measured, and the weight (g) of the foamed beads is divided by the placed volume (1 L) to obtain the bulk density (kg / m) of the foamed beads by unit conversion. 3 ) is calculated. The measurements are carried out under atmospheric pressure at a temperature of 23°C and a relative humidity of 50%.

[0073] The average cell diameter of the expanded beads of the present invention is preferably 50 μm to 900 μm because it provides better moldability, rigidity, dimensional stability, etc. For these reasons, the average cell diameter is more preferably 80 μm to 500 μm, and further preferably 100 μm to 250 μm.

[0074] In this specification, the average cell diameter of expanded beads is measured as follows. A cross section of an expanded bead is bisected and photographed under a microscope at a magnification so that the entire cross section fits within the image. A straight line is drawn on the photograph so as to approximately bisect the cross section, and the length of the line segment from one edge of the expanded bead to the opposite edge (excluding the through-holes) is divided by the number of all cells intersecting the line segment to obtain the average cell diameter of one expanded bead. This operation is performed on 20 randomly selected expanded beads, and the arithmetic mean of the average cell diameters of the 20 expanded beads is defined as the average cell diameter of the expanded beads.

[0075] Next, the method for producing the expanded beads of the present invention will be described. The expanded beads of the present invention can be produced by producing multilayer resin beads (or pellets) having a cylindrical core layer and a coating layer, and expanding the core layer of the obtained multilayer resin beads. In this case, by making the thickness of the coating layer of the multilayer resin beads smaller than the average cell diameter of the expanded beads, it is possible to suppress the expansion of the coating layer during the expansion step of the multilayer resin beads.

[0076] The multilayer resin particles can be obtained by combining a known method, for example, a method for producing resin particles using a die having a die shape similar to the cross-sectional shape shown in Figures 2 and 3 of the present specification as described in JP-A-8-108441, with a method for producing resin particles having a core layer and a coating layer by a co-extrusion method as described in JP-B-41-16125, JP-B-43-23858, JP-B-44-29522, JP-A-60-185816, etc.

[0077] For example, the multi-layer resin particles are produced as follows. An extruder for forming a core layer and an extruder for forming a coating layer are used, and the outlets of both extruders are connected to a co-extrusion die. In the extruder for forming a core layer, a desired resin and additives to be blended as required are melt-kneaded, and in the extruder for forming a coating layer, a desired resin and additives to be used as required are melt-kneaded. The respective melt-kneaded products are merged in the co-extrusion die attached to the tip of the extruder to form a multi-layered resin consisting of a core layer and a coating layer covering the outer surface of the core layer, which is co-extruded in the form of strands from a die having a nozzle of a desired cross-sectional shape, and cut by a pelletizer so that the resin particles have a predetermined weight, thereby producing cylindrical multi-layer resin particles.

[0078] The shape of the multilayer resin particles used in the present invention may be a cylindrical shape such as a cylindrical, elliptical, angular, or combined cylinder shape, etc. The expanded beads obtained by expanding such multilayer resin particles have a shape that generally corresponds to the shape of the resin particles before expansion.

[0079] The average weight per multilayer resin bead is preferably 0.05 mg to 10.0 mg, particularly preferably 0.1 mg to 5.0 mg. The average weight per expanded bead is preferably 0.05 mg to 10.0 mg, particularly preferably 0.1 mg to 5.0 mg, in order to improve the filling into the mold and the fusion between the expanded beads in the mold moldability. The average weight per expanded bead can be adjusted by matching the average weight per multilayer resin bead for obtaining the expanded bead with the average weight per targeted expanded bead.

[0080] In the multilayered resin particles of the present invention, the weight ratio of the core layer to the coating layer (core layer:coating layer) is preferably 99.5:0.5 to 75:25, more preferably 98:2 to 80:20, and further preferably 96:4 to 90:10. When the weight ratio of the coating layer of the multilayer resin beads is within the above range, the fusibility of the resulting expanded beads during molding in a mold is ensured, and the mechanical properties of the resulting expanded bead molding are also good.

[0081] Regarding the thickness of the coating layer of the multilayer resin particle of the present invention, a thinner thickness is preferable in order to prevent bubbles from being generated in the coating layer when the multilayer resin particle is expanded and to improve the mechanical properties of the finally obtained expanded bead molding, but on the other hand, it is preferable to set a lower limit in consideration of the effect of improving the fusibility of the obtained expanded beads. Specifically, the thickness of the coating layer of the multilayer resin particle is preferably 1 μm to 50 μm, more preferably 2 μm to 20 μm, and even more preferably 3 μm to 10 μm.

[0082] The thickness of the coating layer of the multilayer resin particle is measured as follows. The multilayer resin particle is divided into two equal parts so that the cross section surrounded by the coating layer appears, and the thickness is measured by taking a photograph magnified with a microscope so that the entire cross section is included. Specifically, a straight line is drawn on the photograph so that the cross section is approximately divided into two equal parts, and a straight line perpendicular to the straight line and passing through the center of the resin particle is further drawn, and the lengths of the four parts where these straight lines pass through the coating layer are calculated, and the arithmetic average of these is defined as the thickness of the coating layer of one multilayer resin particle. This operation is performed on 10 randomly selected multilayer resin particles, and the arithmetic average of the thicknesses of the coating layers of the 10 multilayer resin particles is defined as the thickness of the coating layer of the multilayer resin particle in this specification. The thickness of the coating layer of the expanded beads is also measured in the same manner. In addition, when it is difficult to determine the thickness of the multilayer resin particle or the coating layer of the expanded beads, multilayer resin particles in which a colorant has been added to the resin constituting the coating layer in advance can be used.

[0083] The expanded beads of the present invention are produced by dispersing multilayer resin particles consisting of the above-mentioned core layer and coating layer in an aqueous medium (usually water) in a pressurizable sealed container (e.g., an autoclave), adding a dispersant, pressurizing in a required amount of foaming agent, and stirring under high temperature and high pressure to impregnate the multilayer resin particles with the foaming agent to form expandable multilayer resin particles, and then releasing the expandable multilayer resin particles together with the aqueous medium from the pressurized container into a pressure region lower than the internal pressure of the container (usually atmospheric pressure) to cause foaming (this method will hereinafter be referred to as the dispersion medium release foaming method). The method for obtaining the expanded beads of the present invention is not limited to the dispersion medium release foaming method, and for example, a method in which resin particles based on the resin composition (a) constituting the core layer are foamed by the dispersion medium release foaming method to produce expanded beads, and the obtained expanded beads are coated with resin powder made of resin (b), etc., can also be used.

[0084] In particular, when expanding beads having a low apparent density (high expansion ratio) are obtained, the expanded beads obtained by the above-mentioned method are subjected to a usual curing under atmospheric pressure, and then stored in a pressurizable airtight container, and a gas such as air is forced into the container to perform a pressurization treatment to increase the internal pressure of the expanded beads. The expanded beads are then removed from the container and expanded again by heating with steam or hot air, thereby obtaining expanded beads having a low apparent density (hereinafter, this method is referred to as a two-stage expansion method).

[0085] The foaming agent is preferably a physical foaming agent. The physical foaming agent is not particularly limited, but for example, organic physical foaming agents such as n-butane, i-butane and their mixtures, aliphatic hydrocarbons such as n-pentane, i-pentane, n-hexane, halogenated hydrocarbons such as ethyl chloride, 2,3,3,3-tetrafluoro-1-propene, trans-1,3,3,3-tetrafluoro-1-propene, etc., and inorganic physical foaming agents such as carbon dioxide, nitrogen, air, water, etc. can be used alone or in combination of two or more. When using an organic physical foaming agent, or a combination of an inorganic physical foaming agent and an organic physical foaming agent, it is preferable to use n-butane, i-butane, n-pentane, i-pentane as the organic physical foaming agent, since they have excellent compatibility with olefin resins and foaming properties. Among these blowing agents, it is preferable to use a blowing agent mainly composed of an inorganic physical blowing agent such as carbon dioxide, nitrogen, or air, and more preferably carbon dioxide is used. In the present invention, "mainly composed of an inorganic physical blowing agent" means that the inorganic physical blowing agent is contained in an amount of 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more of the total physical blowing agents (100 mol %).

[0086] The amount of the physical foaming agent added is appropriately selected depending on the type of propylene-based resin, the type of foaming agent, the apparent density of the target expanded particles, etc., and cannot be generally limited. For example, when carbon dioxide is used as the physical foaming agent, 0.1 to 30 parts by weight, preferably 0.5 to 15 parts by weight, and more preferably 1 to 10 parts by weight is used per 100 parts by weight of the propylene-based resin.

[0087] Examples of dispersants include inorganic substances that are poorly soluble in water, such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, and mica, and water-soluble polymer-based protective colloid agents, such as polyvinylpyrrolidone, polyvinyl alcohol, and methyl cellulose. Also usable are anionic surfactants, such as sodium dodecylbenzenesulfonate and sodium alkanesulfonate.

[0088] When releasing the expandable multilayer resin particles together with the dispersion medium from the sealed container, it is preferable to pressurize the inside of the sealed container (back pressure) with carbon dioxide, nitrogen, etc., and maintain the pressure in the released sealed container constant or adjust the pressure so as to gradually increase it.

[0089] Generally, the temperature rise rate in the foaming step is 0.5° C. / min to 5° C. / min.

[0090] The manufacturing process of the expanded beads of the present invention includes a step of performing a heat treatment by holding the multilayer resin particles in a dispersion medium within a specific temperature range in a closed container before expanding the expandable multilayer resin particles, thereby generating a so-called high-temperature peak. The heat treatment may be performed at any time before, during, or after the impregnation with a blowing agent, or may be performed across two or more of these time points. This heat treatment can obtain expanded beads having a crystal structure that shows a main endothermic melting peak (intrinsic peak) derived from crystals inherent to the polypropylene resin composition (a) and a melting peak (high-temperature peak) located at a higher temperature side than the inherent peak. The heat treatment is performed, for example, as follows. By holding the resin particles for a sufficient time (preferably about 5 to 60 minutes) at a temperature near the melting point (Tm) of the polypropylene resin composition (a) which is the base resin of the multilayer resin particles, more specifically at any temperature within the range of 15°C lower than the melting point (Tm-15°C) or higher and lower than the melting end temperature (Te), a part or all of the crystals inherent to the polypropylene resin composition (a) are melted, and a part of the melted crystals is recrystallized to generate high-potential crystals with thick lamellae. Then, by foaming the expandable multilayer resin particles having these high-potential crystals at the foaming temperature, expanded beads having a crystal structure having crystals (intrinsic crystals) crystallized from the melted crystals by cooling during foaming and high-potential crystals showing a peak on the high-temperature side can be obtained.

[0091] Thereafter, the expandable resin particles are released into a low pressure atmosphere to obtain expanded particles. The temperature of the contents in the sealed container when releasing the expandable resin particles together with the aqueous dispersion medium from the sealed container, i.e., the temperature at which the expandable resin particles are expanded (expansion temperature), is preferably in the range from a temperature (Tm-15°C) 15°C lower than the melting point (Tm) of the polypropylene resin composition (a) to a temperature (Te+10°C) 10°C higher than the melting end temperature. The difference between the pressure in the sealed container and the pressure of the release atmosphere is preferably 1.0MPa to 7.0MPa, more preferably 1.5MPa to 5.0MPa.

[0092] In the dispersion medium release foaming method, the ratio (intrinsic peak heat quantity / high temperature peak heat quantity) can be controlled to 3.5 or more by setting the foaming temperature at a high value or increasing the amount of foaming agent injected.

[0093] The temperature control range during foaming of the resin particles described above is the appropriate temperature range when an inorganic physical foaming agent is used as the foaming agent. When an organic physical foaming agent is used in combination, the appropriate temperature range tends to shift to a lower temperature side than the above temperature range depending on the type and amount of the organic physical foaming agent used due to the plasticizing effect of the organic physical foaming agent on the base resin.

[0094] The expanded polypropylene resin bead molding of the present invention is obtained by molding the expanded propylene resin beads in a mold, and has interconnected voids. Fig. 5 is a schematic diagram showing an example of the surface state of the expanded bead molding of the present invention. Fig. 5 shows an expanded bead molding 1 having a plurality of expanded beads 12 and interconnected voids 6. Thus, the expanded propylene-based resin bead molding of the present invention having interconnected voids has voids 6 as shown in Fig. 5, and is produced by molding the expanded propylene-based resin beads in a mold.

[0095] The method for producing the foamed bead molded article by molding the foamed beads of the present invention in a mold can be exemplified by a known in-mold molding method. For example, a cracking molding method is used in which a pair of molds is used to mold the expanded beads in the mold cavity under atmospheric pressure or reduced pressure, the mold is closed to compress the mold cavity volume to reduce the volume by 5% to 50% by volume, and then a heating medium such as steam is supplied into the mold to heat-seal the expanded beads (e.g., JP-B-46-38359). Alternatively, the expanded beads can be molded by a pressure molding method in which the expanded beads are pressurized with a pressurized gas such as air to increase the pressure inside the expanded beads, the expanded beads are filled into the mold cavity under atmospheric pressure or reduced pressure, the mold is closed, and then a heating medium such as steam is supplied into the mold to heat-seal the expanded beads (e.g., JP-B-51-22951). Molding can also be performed by a compression filling molding method (e.g., JP-B-4-46217) in which the foamed particles are filled into a mold cavity pressurized to atmospheric pressure or higher by a compressed gas, and then a heating medium such as steam is supplied into the mold to heat-fuse the foamed particles. Molding can also be performed by a normal pressure filling molding method (e.g., JP-B-6-49795) in which the foamed particles are filled into a pair of mold cavities under atmospheric pressure, and then a heating medium such as steam is supplied to heat-fuse the foamed particles, or a combination of the above methods (e.g., JP-B-6-22919).

[0096] The density of the foamed bead molding produced by molding the foamed bead of the present invention in a mold is set to 15 to 50 kg / m in order to achieve both light weight and rigidity. 3 It is preferable that the range is 20 to 40 kg / m 3 It is.

[0097] The density of the foamed bead molding (kg / m 3 ) is calculated by dividing the weight (g) of the molded body by the volume (L) determined from the outer dimensions of the molded body, and converting the result into units.

[0098] The porosity of the expanded bead molding of the present invention is preferably 20% or more. If the porosity is 20% or more, an expanded bead molding excellent in sound absorption, air permeability, water permeability, vibration resistance, etc. can be obtained. In addition, when the molding is used as an automobile part, the effect of improving the adhesion to polyurethane foam can be obtained. For these reasons, the porosity of the molding is more preferably 22% or more, and even more preferably 24% or more. The upper limit is about 40%, preferably 35%.

[0099] The porosity of the expanded bead molding can be calculated as follows: A cubic test piece cut out of the expanded bead molding by removing the skin is immersed in a volume of alcohol, and the true volume of the test piece, Vt (cm), is calculated from the rise in the level of the alcohol. 3 ) is calculated from the external dimensions of the test piece (length x width x height). 3 The void ratio of the foamed bead molding is calculated from the obtained true volume Vt and apparent volume Va according to the following formula. Porosity (%)=[(Va-Vt) / Va]×100

[0100] The expanded bead molding of the present invention has an excellent balance between the rigidity and the cushioning properties of the molding, and therefore the 50% compressive stress of the expanded bead molding is preferably 120 to 300 kPa, more preferably 150 to 250 kPa, and even more preferably 185 to 240 kPa. When the 50% compressive stress is within this range, the generation of scraping noise when the molding is used as an automobile part is more easily suppressed. The 50% compressive stress is a measure of the rigidity of the expanded molding.

[0101] The 50% compressive stress of the expanded bead molding is measured as follows. A test piece measuring 50 mm in length, 50 mm in width, and 25 mm in thickness is cut out from the foamed bead molding, excluding the skin layer, and the compressive stress (MPa) at 50% strain when compressed at a rate of 10 mm / min is measured based on JIS K 6767:1999.

[0102] The expanded beads of the present invention have excellent fusion properties between the expanded beads and can be molded in a mold at a wider range of molding steam pressures than conventional expanded beads. The obtained expanded bead molding has a high porosity and is endowed with desired properties such as air permeability, water permeability, sound absorption, sound deadening, and vibration isolation due to the interconnected pores, and has good mechanical properties, so that it can be suitably used as a drainage material, a wall material in a building, an automobile interior material, a cushioning material, etc. In addition, since it has excellent adhesion to polyurethane foam, it can also be suitably used as an automobile member such as an automobile seat member. EXAMPLES

[0103] The present invention will now be described in more detail with reference to examples, although the present invention is not limited to these examples in any way.

[0104] In the examples and comparative examples, the resins shown in Table 1 were used.

[0105] [Table 1]

[0106] In Table 1, the melting points and heat of fusion were measured as follows. Based on the heat flux differential scanning calorimetry method described in JIS K7121:2012, 2 mg of the pellet-shaped base resin was used as a test piece, and the temperature was raised from 30°C to 200°C at a heating rate of 10°C / min, then cooled to 30°C at a cooling rate of 10°C / min, and then heated again from 30°C to 200°C at a heating rate of 10°C / min. The apex temperature of the endothermic peak determined by the DSC curve obtained when the temperature was raised from 30°C to 200°C at a heating rate of 10°C / min was taken as the melting point of the resin. The area of ​​the endothermic peak was taken as the heat of fusion of the resin. The measurement device used was a heat flux differential scanning calorimeter (manufactured by TA Instruments: DSC Q1000).

[0107] In Table 1, the flexural modulus of the resin was measured in accordance with JIS K7171:2008. The test piece was prepared by heat pressing the resin at 230°C to produce a 4 mm sheet, and cutting the sheet into a length of 80 mm x width of 10 mm x thickness of 4 mm (standard test piece). The radius R1 of the indenter and the radius R2 of the support table were both 5 mm, the distance between the supports was 64 mm, and the test speed was 2 mm / min.

[0108] In Table 1, the MFR was measured by the above-mentioned method. Specifically, in accordance with JIS K7210-1:2014, the polypropylene resin was measured at a temperature of 230°C and a load of 2.16 kg, and the polyethylene resin was measured at a temperature of 190°C and a load of 2.16 kg.

[0109] Air Foam Control Agent Masterbatch A cell regulator master batch was used, which was made by blending 10% by weight of zinc borate with 90% by weight of polypropylene resin.

[0110] In the examples and comparative examples, multi-layered resin particles were formed using the following equipment. An extruder with an inner diameter of 100 mm and L / D = 32 was used as the extruder for forming the foamed core layer, and an extruder with an inner diameter of 25 mm and L / D = 32 was used as the extruder for forming the coating layer.Furthermore, the outlets of the extruder for forming the foamed core layer and the extruder for forming the coating layer were connected to a co-extrusion annular die, making it possible to stack the respective resin melts within the co-extrusion annular die.

[0111] Examples 1 to 5, Comparative Examples 1 to 5 (Production of multi-layered resin particles) The resin for forming the foamed core layer and the foaming agent master batch shown in Tables 2 and 3 were fed to the first extruder in an amount of 5 parts by weight per 100 parts by weight of the resin for forming the core layer, and melt-kneaded to form a resin melt for forming the foamed core layer. At the same time, the resin for forming the coating layer shown in Tables 2 and 3 was fed to the third extruder, melt-kneaded to form a resin melt for forming the coating layer. The resin melt for forming the foamed core layer and the resin melt for forming the coating layer were introduced into a co-extrusion die, and the resin melt for forming the coating layer was laminated around the resin melt for forming the foamed core layer so that the coating layer had the weight ratio shown in Tables 2 and 3. A multilayer strand in which a coating layer was formed on the outer periphery of a cylindrical core layer having a through hole was co-extruded from a small hole in the co-extrusion die attached to the tip of the extruder, and then the strand was water-cooled, cut with a pelletizer so that the weight was about 1.5 mg, and dried to obtain multilayer resin particles. In producing the multilayered resin particles, the hole size of the die was adjusted so that the average outer diameter D0, average pore diameter d0, and average wall thickness t0 of the resin particles were the values ​​shown in Tables 2 and 3. The average outer diameter D0, average pore diameter d0, and average wall thickness t0 of the resin particles were measured in the same manner as the average outer diameter D, average pore diameter d, and average wall thickness t of the expanded beads described above.

[0112] [Table 2]

[0113] [Table 3]

[0114] (Production of expanded beads) Next, the multi-layered resin particles were used to prepare expanded propylene-based resin particles. First, 1 kg of the multilayer resin particles obtained as described above was placed in a 5 L sealed container equipped with a stirrer together with 3 L of water as a dispersion medium, and further, 0.3 parts by weight of kaolin as a dispersant, 0.004 parts by weight of a surfactant (product name: NEOGEN S-20F, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., sodium alkylbenzene sulfonate) as an active ingredient, and carbon dioxide as a foaming agent were injected into the dispersion medium to the pressures (CO injection pressures) shown in Tables 4 and 5. Next, the temperature of the dispersion medium was raised to "expansion temperature - 5°C" under stirring and maintained at that temperature for 15 minutes. Thereafter, the temperature was raised to the expansion temperature shown in Tables 4 and 5 and maintained at that temperature for 15 minutes, and then the contents were released under atmospheric pressure while applying the back pressure shown in Tables 4 and 5 with carbon dioxide, thereby obtaining roughly cylindrical expanded beads having through holes. The physical properties of the obtained expanded beads are shown in Tables 4 and 5. The amounts (parts by weight) of the dispersant and surfactant added are based on 100 parts by weight of the propylene-based resin particles.

[0115] [Table 4]

[0116] [Table 5]

[0117] The obtained expanded beads had a cylindrical shape as shown in Figure 1. When the cross section of the expanded beads was observed under an optical microscope, the resin constituting the expanded core layer was well expanded to form a closed cell structure, while the resin constituting the coating layer was not expanded.

[0118] The average inner diameter d of the through holes of the expanded beads and the average outer diameter D of the expanded beads were measured by the above-mentioned method. In measuring the average inner diameter d of the through holes of the expanded beads, the expanded beads were first cut perpendicularly to the penetration direction of the through holes at the position where the area of ​​the cut surface was maximum. A photograph of the cut surface of the expanded beads obtained was taken, and the area of ​​the through hole part in the photograph (i.e., the cross-sectional area of ​​the through hole) was obtained, and the diameter of a virtual perfect circle having the same area as that area was calculated, and this value was taken as the hole diameter of the through holes of the expanded beads. The above-mentioned measurement was performed on 50 expanded beads, and the arithmetic average value thereof was taken as the average hole diameter d of the expanded beads. In measuring the average outer diameter D of the expanded beads, the expanded beads were first cut perpendicularly to the penetration direction of the through holes at the position where the area of ​​the cut surface was maximum. A photograph of the cut surface of the expanded beads was taken, and the area of ​​the expanded beads in the photograph (i.e., the cross-sectional area of ​​the expanded beads including the cross-sectional area of ​​the through holes) was determined. The diameter of a virtual circle having the same area as the area was calculated, and this value was taken as the outer diameter of the expanded beads. The above measurement was performed on 50 randomly selected expanded beads, and the arithmetic average value was taken as the average outer diameter D of the expanded beads. The average thickness t of the expanded beads was calculated based on (Dd) / 2. The results are shown in Tables 4 and 5.

[0119] The bulk density of the expanded beads was measured by the method described above. Specifically, expanded beads were randomly taken from the expanded bead group and placed in a measuring cylinder with a volume of 1 L, and a large number of expanded beads were placed up to the 1 L mark so as to form a natural pile-up state, and the mass W1 [g] of the placed expanded beads was measured. This operation was carried out five times for different expanded bead samples, and the bulk density of each expanded bead sample was calculated from each measured value and converted into units, and the arithmetic average of these values ​​was determined as the bulk density of the expanded beads (kg / m 3 ) was decided.

[0120] The melting point of the expanded beads was measured by the above-mentioned method. As a specific example, 3 mg of the expanded beads was used as a test piece, and based on the heat flux differential scanning calorimetry method described in JIS K7121:2012, the test piece was heated from 30°C to 200°C at a heating rate of 10°C / min, cooled to 30°C at a cooling rate of 10°C / min, and then heated again from 30°C to 200°C at a heating rate of 10°C / min. The apex temperature of the endothermic peak determined by the DSC curve obtained when the test piece was heated from 30°C to 200°C at a heating rate of 10°C / min was taken as the melting point of the expanded beads. The measurement device used was a heat flux differential scanning calorimeter (manufactured by TA Instruments: DSC Q1000).

[0121] The high-temperature peak calorific value and the intrinsic peak calorific value (low-temperature peak calorific value) of the expanded beads were measured by a measurement method conforming to JIS K7122:2012, as described above. First, about 3 mg of the expanded beads were collected, and the temperature was increased from 30°C to 200°C at 10°C / min using a heat flux differential scanning calorimeter to obtain a DSC curve. In the following explanation, the resin intrinsic peak was designated A, and the high-temperature peak appearing on the higher temperature side was designated B. A straight line (α-β) was drawn connecting point α corresponding to 80°C on the DSC curve and point β on the DSC curve corresponding to the melting end temperature T of the expanded beads. The melting end temperature T refers to the intersection point between the DSC curve on the high-temperature side of the high-temperature peak B and the high-temperature side baseline. Next, a straight line parallel to the vertical axis of the graph was drawn from point γ on the DSC curve corresponding to the valley between the resin intrinsic peak A and the high-temperature peak B, and the point of intersection with the straight line (α-β) was designated σ. The area of ​​high-temperature peak B is the area surrounded by the curve of the high-temperature peak B part of the DSC curve, the line segment (σ-β), and the line segment (γ-σ), and this was defined as the high-temperature peak heat quantity ΔHh. The area of ​​the intrinsic peak is the area surrounded by the curve of the resin intrinsic peak A part of the DSC curve, the line segment (α-β), and the line segment (γ-σ), and this was defined as the intrinsic peak heat quantity (low-temperature peak heat quantity) ΔHm. The total heat of fusion of the expanded beads was calculated as the sum of the high-temperature peak heat and the main endothermic peak heat (intrinsic peak heat). The measurement was performed using a heat flux differential scanning calorimeter (TA Instruments: DSC Q1000).

[0122] <Production of foamed bead molded body> The resulting expanded beads were used to carry out molding into an expanded bead molding. First, the expanded beads were filled into a flat mold measuring 300 mm long x 250 mm wide x 60 mm thick, and molding was performed in the mold by pressure molding using steam as a heating medium to obtain a flat expanded bead molding. The heating method used during in-mold molding was as follows: with the drain valves on both sides of the mold open, steam was supplied for 5 seconds to preheat, followed by one-way heating at a pressure 0.04 MPa (G) lower than the molding steam pressure shown in Tables 6 and 7, and then one-way heating from the opposite direction at a pressure 0.02 MPa (G) lower than the molding steam pressure shown in Tables 6 and 7, and then heating with steam at the molding steam pressure [MPa (G): gauge pressure] shown in Tables 6 and 7. After heating, the pressure was released and the mold was cooled with water until the value of the pressure gauge attached to the inner surface of the mold dropped to 0.04 MPa (G), after which the mold was opened and the molded product was removed from the mold. The molded product obtained was cured in an oven at 60°C for 12 hours and then slowly cooled to obtain an expanded bead molded product. The physical properties of the obtained molded product are shown in Tables 6 and 7. In this way, an expanded bead molded product having a flat plate shape with a thickness of 60 mm and interconnected voids was obtained. The physical properties and fusion properties of the expanded bead molded product are shown in Tables 6 and 7.

[0123] [Table 6]

[0124] [Table 7]

[0125] In Tables 6 and 7, "steam pressure range 1" is the moldable range, in which the molding steam pressure is changed between 0.08 and 0.30 MPa (G) in increments of 0.02 MPa (G) to mold an expanded bead molding, and the obtained molding is evaluated for two items, fusion property and recovery property, according to the criteria described below. Products that achieve an A rating in both items are deemed to pass, and this means the range of steam pressure at which a passing product was obtained. Expanded beads with a wider range from the lower limit to the upper limit of the moldable steam pressure are judged to have a wider moldable range and to have better in-mold moldability. Expanded beads with a lower moldable steam pressure are judged to be moldable at a lower pressure and to have better in-mold moldability.

[0126] In Tables 6 and 7, "Steam pressure range 2" refers to the range in which a high porosity molding can be obtained, and refers to the molding steam pressure range in which the porosity of the expanded bead molding obtained in the molding process was measured and a foamed bead molding with a porosity of 20% or more could be obtained within the above-mentioned moldable range.

[0127] In Tables 6 and 7, the physical properties and evaluations were determined as follows. (Density of foamed bead molding) The density of the expanded bead molding (with skin) was calculated by dividing the weight (g) of the molded body with the skin obtained by in-mold molding by the volume (L) calculated from the outer dimensions of the molded body. The measurement was performed on the expanded bead molding aged for 48 hours under atmospheric pressure at a temperature of 23°C and a relative humidity of 50%.

[0128] The void ratio of the expanded bead molding was determined by the above-mentioned method. Specifically, a cubic test piece of 20 mm length × 100 mm width × 20 mm thickness was cut out from the expanded bead molding by removing the skin, and was immersed in a volume of alcohol, and the true volume Vt (cm) of the test piece was calculated from the rise in the liquid level of the alcohol. 3 Next, the apparent volume Va (cm ) was calculated from the outer dimensions of the test piece. 3 The void ratio of the expanded bead molding was calculated from the calculated true volume Vt and apparent volume Va according to the above formula (2).

[0129] (Shrinkage rate) The molding shrinkage rate of the expanded bead molding was measured as follows. The shrinkage rate [%] of the expanded bead molding was calculated by (300 [mm] - long side length of the molding [mm]) / 500 [mm] x 100. Here, "300 [mm]" is the long side dimension of the molding die. Furthermore, "long side length of the molding [mm]" refers to the value measured for the long side length of the expanded bead molding obtained in the examples and comparative examples after curing in an atmosphere of 80°C for 12 hours, slowly cooling, and further curing in an atmosphere of 23°C for 6 hours.

[0130] (Evaluation of fusion property of foamed beads) The expanded bead molding was bent and broken, and the fracture surface was observed to determine the number of broken expanded beads present on the fracture surface divided by the total number of expanded beads present on the fracture surface. The material failure rate (%) was calculated and evaluated according to the following criteria. A: When the foamed bead molding is broken, the material destruction rate of the foamed bead is 90% or more. B: The material destruction rate of the foamed beads when the foamed bead molding is broken is less than 90%.

[0131] (Evaluation of recovery of expanded particles) Molding was performed in a flat mold measuring 300 mm in length, 250 mm in width, and 60 mm in thickness, and the thickness of the obtained foamed bead molding was measured near the four corners (10 mm inward from the corners toward the center) and at the center (the part that divides the thickness into two equal parts in both the length and width directions). Next, the ratio (%) of the thickness at the center to the thickness at the thickest point near the four corners was calculated, and a ratio of 90% or more was given an A rating, and a ratio of less than 90% was given a B rating.

[0132] (Compressive stress at 50% strain) A test piece measuring 50 mm long x 50 mm wide x 25 mm thick was cut out from the center of the expanded bead molding, excluding the skin, and a compression test was performed at a compression speed of 10 mm / min based on JIS K6767 (1999) to determine the 50% compressive stress of the expanded bead molding. The density of the test piece used in this measurement is shown in the table as the density of the expanded bead molding (without skin). The density of the expanded bead molding (without skin) was measured in the same manner as in the measurement of the density of the expanded bead molding, except that a test piece cut out from the molding after removing the skin was used.

[0133] The expanded beads of the examples of the present invention could be used to mold expanded bead moldings with high porosity over a wide range of molding steam pressures. Specifically, the expanded beads of the present invention could be molded in a mold at a low molding steam pressure of about 0.12 MPa (G). Even under a high molding steam pressure of 0.20 MPa, an expanded bead molding with a porosity of 20% or more could be obtained. The obtained moldings were lightweight and had excellent rigidity. Moreover, in Example 3 in which the content of the high melting point resin PP2 was 5% by weight, the lower limit of the moldable water vapor pressure was a particularly low value of 0.10 MPa (G).

[0134] Comparative Example 1 is an example in which the foamed core layer is formed by only the low melting point resin PP1 without the inclusion of the high melting point resin PP2, and the ratio of the intrinsic peak heat quantity / high temperature peak heat quantity is low. The molding water vapor pressure was high, and the moldable range was narrow. In addition, the compressive stress at 50% strain was somewhat low.

[0135] In Comparative Example 2, the foamed core layer was formed using only the low melting point resin PP1 without the inclusion of the high melting point resin PP2, and the ratio of the intrinsic peak heat quantity / high temperature peak heat quantity was approximately the same as that of Example 1. Low pressure molding was possible, but the compressive stress at 50% strain was somewhat low. In addition, the void ratio decreased under conditions of high molding steam pressure.

[0136] Comparative Example 3 is an example in which the high melting point resin PP2 was contained in a large amount of 40% by weight. The influence of the high melting point resin PP2 was large, and the molding vapor pressure was high.

[0137] Comparative Example 4 is an example in which the low melting point resin PP1 was replaced with the low melting point resin 2. Under conditions of high molding vapor pressure, the porosity decreased.

[0138] Comparative Example 5 is an example in which the resin composition was the same as that of Example 1, and the intrinsic peak heat quantity / high-temperature peak heat quantity was controlled to be small by increasing the expansion temperature. The molding steam pressure was high, and the compressive stress at 50% strain of the obtained expanded bead molding was also slightly low. In Comparative Examples 1, 3, and 5, the lower limit of "steam pressure range 1" was high, and the low-pressure moldability was poor, so "steam pressure range 2" was not evaluated. [Explanation of symbols]

[0139] 1. Expanded bead molding 2. Foam particles 3. Foam core layer 4 Through holes 5 Covering layer 6 void 12. Foam particles

Claims

1. An expanded bead having a through hole, The expanded beads have a cylindrical expanded core layer having the through holes formed therein and made of a polypropylene-based resin composition, and a coating layer covering the expanded core layer and made of a polyolefin-based resin, The polypropylene-based resin composition comprises 70 to 97% by weight of a propylene-based resin PP1 having a melting point of more than 140° C. and not more than 150° C., and 3 to 30% by weight of a polypropylene-based resin PP2 having a melting point of 145° C. or more and not more than 160° C. (the total amount of the resins PP1 and PP2 is 100% by weight). the difference between the melting point of the polypropylene-based resin PP2 and the melting point of the polypropylene-based resin PP1 [(melting point of PP2) - (melting point of PP1)] is 5°C or more and less than 15°C; the expanded beads have a crystal structure that gives a first DSC curve when measured by heat flux differential scanning calorimetry in which the expanded beads are heated from 30° C. to 200° C. at a heating rate of 10° C. / min; The first DSC curve has a main endothermic peak specific to the polypropylene-based resin composition and a high-temperature endothermic peak located on the high-temperature side of the main endothermic peak, the heat quantity of the high-temperature endothermic peak is 12 to 20 J / g, and the ratio of the heat quantity of the main endothermic peak to the heat quantity of the high-temperature endothermic peak is 3.5 or more; The polyolefin resin of the expanded polypropylene resin particles satisfies the following (I) or (II): (I) When the polyolefin resin is a crystalline polyolefin resin, the polyolefin resin has a melting point (TmB) lower than the melting point (TmA) of the polypropylene resin composition, and the difference between the melting point (TmA) and the melting point (TmB) [TmA-TmB] is greater than 0°C and not greater than 80°C. (II) When the olefin resin is an amorphous polyolefin resin, the olefin resin has a softening point (TsB) lower than the melting point (TmA) of the polypropylene resin composition, and the difference between the melting point (TmA) and the softening point (TsB) [TmA-TsB] is greater than 0°C and not greater than 100°C.

2. The polypropylene-based resin expanded particles according to claim 1, wherein the polypropylene-based resin PP1 has a melting point of more than 140°C and not more than 145°C, and the polypropylene-based resin PP2 has a melting point of 150°C or more and 155°C or less.

3. 3. The polypropylene-based resin expanded particles according to claim 1, wherein the polypropylene-based resin PP2 has a melt flow rate (MFR) of 2 to 18 g / 10 min at 230° C. under a load of 2.16 kg.

4. The polypropylene-based resin expanded particles according to any one of claims 1 to 3, wherein the polypropylene-based resin PP1 and the polypropylene-based resin PP2 are each obtained by polymerization in the presence of a Ziegler-Natta polymerization catalyst.

5. The bulk density of the expanded particles is 15 to 50 kg / m 3 The expanded polypropylene resin particles according to any one of claims 1 to 4,

6. A polypropylene-based resin foamed particle described in any one of claims 1 to 5, wherein the foamed beads have an average outer diameter D (mm), an average pore diameter d (mm) of the through holes of the foamed beads, and an average wall thickness t (mm) defined as (D-d) / 2, wherein t is 0.8 to 2 mm and t / d is 0.4 to 1. However, the average outer diameter D and the average pore diameter d of the through holes are calculated as follows. The average outer diameter D of the expanded beads is determined by cutting the expanded beads perpendicularly to the penetration direction of the through holes at the position where the area of ​​the cut surface is maximum, taking a photograph of the cut surface of the expanded beads, determining the area of ​​the expanded beads in the photograph (i.e., the cross-sectional area of ​​the expanded beads including the cross-sectional area of ​​the through holes), calculating the diameter of a virtual perfect circle having the same area as the area, and determining the value as the outer diameter of the expanded beads. The above measurement is performed on 50 randomly selected expanded beads, and the arithmetic average value thereof is determined as the average outer diameter D of the expanded beads. The average pore diameter d of the through holes of the expanded beads is determined by cutting the expanded beads perpendicularly to the penetration direction of the through holes at the position where the area of ​​the cut surface is maximum, taking a photograph of the cut surface of the expanded beads obtained, determining the area of ​​the through holes in the photograph (i.e., the cross-sectional area of ​​the through holes), calculating the diameter of an imaginary perfect circle having the same area as that area, and determining this value as the pore diameter of the through holes of the expanded beads. The above measurement is performed on 50 expanded beads, and the arithmetic average value thereof is determined as the average pore diameter d of the expanded beads.

7. 7. A polypropylene-based resin expanded bead molding comprising a large number of expanded beads according to any one of claims 1 to 6 fused to one another, the expanded bead molding having interconnected voids and a void ratio of 20% or more.

Citation Information

Patent Citations

  • Method for producing molded body of expanded polyolefin resin particle, and molded body of expanded polyolefin resin particle

    JP2012126816A

  • Vehicular interior material made of molded article of polyolefin resin foamed particle

    JP2015137061A

  • Vehicle seat member

    JP2019030597A

  • US10,487,188

  • Process for producing molded body of expanded polyolefin resin particles, and molded body of expanded polyolefin resin particles

    WO2012081490A1